Analisis Pencahayaan Alami dan Buatan pada Ruang Ujian II Fakultas Teknik Universitas Muhammadiyah Kendari - La Ode Arjuna Pratama; Wulandari Wanda; La Pande Jurumai (Jurnal Inovasi Sains dan Teknologi (INSTEK), 2022)
Lighting is one factor that really supports the achievement of a function in space optimally. Lighting Natural and artificial lighting have their respective roles in their use, so both must be utilized properly in order to create an optimal comfort and function of these factors and there is no excessive use of natural and artificial lighting. This analysis was carried out in order to determine the level of optimization of natural and artificial light in the examination room II of the Faculty of Engineering, Muhammadiyah University of Kendari. So that in the future it can be a reference for designers in designing buildings or spaces in terms of optimizing the use of natural and artificial light.